6.2 Atosiban activates NF-κB and pro-inflammatory pathways in human amnion via Gαi signalling. (9th June 2014) - Kim, SH; Blanks, A; Thornton, S; Bennett, PR; Terzidou, V
Abstract : Inflammation is recognized as one of the key characteristics of both preterm and term labour. There is accumulating evidence suggesting that NF-κB plays a significant role in the physiology of human labour. NF-κB has been shown to increase in human amnion in association with labour. In term pre-labour amniocytes, OT couples with Gαi, but not Gαq, to induce sequential activation of MAPKs and NF-κB to increase expression of downstream pro-labour genes including PG synthetic enzymes and inflammatory cytokines/chemokines. We have previously reported that the OTR antagonist, atosiban, does not inhibit, but stimulates both MAPKs and NF-κB in amnion. Here, we investigate the downstream effects of NF-κB activation by atosiban and the relevant G protein coupling involved. Following activation of MAPKs and NF-κB with atosiban stimulation, there were significant increases in mRNA expressions of NF-κB-regulated genes; IL-6, CCL5, and COX-2, and increases in the release of IL-6 and CCL5 after 2 h and 6 h, respectively ( p < 0.05, ANOVA). In addition, upregulation of COX-2 and activation of cPLA2 were observed at protein level, as well as the subsequent PGE2 production ( p < 0.05, ANOVA). Pretreatment with PTX reduced the effect of atosiban on NF-κB, ERK and p38 activation, and inhibited COX-2 and p-cPLA2 expression, indicating that these effects are mediated through Gαi ( p < 0.05, ANOVA). We conclude that atosiban induces activation of NF-κB and increase expression of downstream pro-labour genes via OTR- Gαi coupling. Therefore, therapeutic modulation of the OT/OTR system for clinical management of term/preterm labour should consider potential inflammatory activation by ligand-directed signalling.